Physiological Difference of Estrus and Pregnant Ovary in Korean Water Deer - Sang-Hwan Kim; Ho-Jun Lee; Joo-Yong Lee; Yong-Su Park; Jong-Taek Yoon (Journal of Animal Reproduction and Biotechnology, 2014)
To describe the macroscopic anatomy and ovarian-physiological difference of the genital organs of the female Korean water deer, organs from captured animals in a wild area of Korea were dissected. The ovary of estrus group was about 1.10 ± 0.02 mm long and weighed about 0.50 ± 0.02 g. And pregnant group was about 1.3 ± 0.10 mm long and weighed about 0.40 ± 0.05 g. And the crowns of corpora lutea were found in the estrus group, but we couldn't find crowns at the pregnant group. Especially, the estrus ovaries tended (p=0.04) to be heavier than the ovaries during pregnancy. The MMP-9 activity was higher at the Graafian follicles of pregnant group than that in estrus group. However, with regard to follicles of estrus group, MMP-2 level was higher than that in pregnant group. Furthermore, apoptosis detection marker (Casp-3) was highly expressed in Graafian follicle of the pregnant group and the corpora lutea of estrus group. Thus, the differential expression of MMPs observed in this study suggests that the reflected the mechanisms underlying of monovulatory in estrus and/or pregnancy. Our results may be very useful as it provides with information that may be considered for the development of reproductive biotechnologies in endangered animals.